Pengaruh Pajak Daerah dan Retribusi Daerah terhadap Belanja Langsung pada Kota Banda Aceh - Ardian; Devi Mulia Sari; Rajuaini (Jurnal Penelitian Ekonomi Akuntansi, 2023)
This study aims to determine the effect of local taxes and regional levies on direct spending in Banda Aceh City in the 2017-2020 period. The phenomenon found was a decrease in the total value of Original Local Government Revenue in 2020, along with refocusing and reallocation of the budget as a result of the Covid-19 pandemic. The type of data used in this study is secondary data consisting of the Banda Aceh City Government Budget Realization Report (LRA) for 2017-2020. The data processing technique used in this research is multiple linear regression analysis and hypothesis testing is processed with SPSS 25.0. The results of data analysis show that local taxes and regional levies partially have no effect on direct spending. The results also show that local taxes and regional levies simultaneously have no effect on direct spending.